Pendampingan Penguatan Profil Pelajar Pancasila Melalui Program Pengelolaan Sampah dengan Prinsip 5R berbasis Edukasi dan Sedekah Sampah - Apriani, Ani; Trisnaning, Paramitha Tedja; Fatimah; Marsyom, Insren Loisa; Chalista, Angel Ribka; Putri, Rizky Eka; Cahyo, Gilang Ramadhan Dwi (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2025)
Waste management issues in schools are often caused by a lack of awareness and understanding among students regarding the importance of sorting and managing waste properly. The mentoring program for the Projek Penguatan Profil Pelajar Pancasila (P5) at SDIT Salsabila Baiturahman aims to improve students’ awareness and understanding of waste management based on the 5R principles (Refuse, Reduce, Reuse, Recycle, Repair) and implement the Sedekah Sampah program. The program was conducted through educational activities, including counseling and workshops, as well as the implementation of the Sedekah Sampah program. Results indicated a significant improvement in students’ understanding of waste management, as evidenced by the Wilcoxon Signed Ranks Test (p-value = 0.000). The implementation also successfully supported school activities using funds generated from waste sales. This program contributes to character building in students, particularly in environmental awareness and collaboration, aligning with P5 goals.